Outcome of Piercing Auricular Keloid After Surgical Excision by Through-and-Through Technique and Adjuvant Triamcinolone Acetonide Injection - Jaruniphakul, Kollawat; Awsakulsutthi, Surajit; Kitvoraphat, Kornpong; Saengpongpithaya, Tirakorn; Singnoo, Attawat (Asian Medical Journal and Alternative Medicine, 2021)
Introduction: Keloids are benign fibrous proliferative tissues resulting from pathological wound healing process. Auricular keloids are the challenging problem to cope with due to their resistanceto various modalities of treatment and having a high recurrence rate. There are no standard protocols for the treatment of ear keloids in the present practice. The purpose of this study is to introduce and evaluate the effectiveness of the practical treatment protocol for treating auricular keloids by using the modified surgical technique called “Through-and-Through excision technique” and postoperative intralesional TriamcinoloneAcetonide (TA) injection as an adjuvant therapy. Methods: We retrospectively analyzed all patients who present with piercing auricular keloids at Plastic Surgery Outpatient Clinic, Thammasat University Hospital between June 2017 and March 2019. Forty one patients representing with forty nine keloids were treated by a single Plastic Surgeon. Every patient received surgery and intralesional TA injection at 2-week postoperative time period. TA injection was considered every 1 month for the individual patient. Results were evaluated at one year after the operation. Results: The patients’ ages ranged from 16 to 58 years old (mean age: 24 years old). The mean size of keloid is 1.6 cm which ranged from 0.5 to 5 cm. The treatment protocol achieved a 94% successrate in 1-year of follow-up with only three keloids(6%) which developed recurrence. Conclusions: Surgical excision by Through-and-Through technique with postoperative intralesional TA injection is one of the alternatives and beneficial modalities which can be used effectively for patients with piercing auricular keloids due to its excellent results and cost-effectiveness.